Overcoming smallholder farmers’ post-harvest constraints through harvest loans and storage technology: insights from a randomized controlled trial in Tanzania - Channa, H.; Ricker-Gilbert, J.; Feleke, S.; Abdoulaye, Tahirou (Elsevier, 2022)
Maintaining staple grains throughout the year and managing liquidity are two major challenges that smallholder farmers face at harvest. We implemented a randomized controlled trial in Tanzania that was designed to address these post-harvest constraints. First, we offered treated farmers two hermetic (airtight) storage bags, which helped preserve grain quantity and quality. Second, we offered other treated farmers a loan at harvest, which reduced the liquidity constraints they faced. Repayment was due with interest six months from harvest when maize prices were traditionally higher. We did not find a significant impact of the storage intervention. However, those offered the loan stored 29 percent more and sold 50 percent more maize on average in the lean season compared to farmers in the control group. Nevertheless, an unexpected maize export ban in Tanzania likely attenuated the outcomes of both interventions. This highlighted the challenges surrounding agricultural financial products in the developing world.